Thermodynamic prediction of martensitic transformation temperature in Fe-Ni-C system. (October 2020) - Luo, Qun; Chen, Hongcan; Chen, Wei; Wang, Chenchong; Xu, Wei; Li, Qian
Abstract: The martensite start temperature ( M s ) is a significant parameter to describe the stability of retained austenite in steels. This paper provides a prediction model of M s for lath martensite considering chemical and non-chemical driving forces. The non-chemical driving force includes shearing energy of austenite, dilatation strain energy of martensite and dislocation stored energy, where dilatation strain energy and dislocation stored energy provide the major contribution. Based on the calculation method, the contour lines of transformation driving forces and M s in Fe-Ni-C system are predicted which agrees with experimental data with calculation error of 4.6%. Graphical abstract: Image, graphical abstract